Role of macrophage migration inhibitory factor (MIF) in murine antigen-induced arthritis: interaction with glucocorticoids - Santos, L (Blackwell Science Inc, 2001)
(MIF) is a broad-spectrum proinflammatory cytokine implicated in human rheumatoid arthritis. The synthesis of MIF by synovial cells is stimulated by glucocorticoids, and previous studies suggest that MIF antagonizes the anti-inflammatory effects of glucocorticoids. This has not been established in a model of arthritis. We wished to test the hypothesis that MIF can act to reverse the anti-inflammatory effects of glucocorticoids in murine antigen-induced arthritis (AIA). Cutaneous DTH reactions and AIA were induced by intradermal injection and intra-articular injection, respectively, of methylated bovine serum albumin in presensitized mice. Animals were treated with anti-MIF MoAbs, recombinant MIF, and/or dexamethasone (DEX). Skin thickness of DTH reactions was measured with callipers and arthritis severity was measured by blinded quantitative histological assessment of synovial cellularity. Cutaneous DTH to the disease-initiating antigen was significantly inhibited by anti-MIF MoAb treatment (P < 0·001). AIA was also significantly inhibited by anti-MIF MoAb (P < 0·02). DEX treatment induced a dose-dependent inhibition of AIA, which was significant at 0·2 mg/kg (P < 0·05). MIF treatment reversed the effect of therapeutic DEX on AIA (P < 0·001). DEX also significantly inhibited DTH reactions (P < 0·05) but rMIF had no effect on this effect of DEX. DTH and AIA are MIF-dependent models of inflammation and arthritis. The reversal of glucocorticoid suppression of AIA by MIF supports the concept that MIF is a counter-regulator of glucocorticoid control of synovial inflammation. Although DTH was observed to be MIF-dependent and glucocorticoid-sensitive, rMIF had no reversing effect on the suppression of DTH by glucocorticoids. This suggests that inflammatory processes in specific tissues may respond differently to MIF in the presence of glucocorticoids.